Willingness to pay for packaging cancer screening of Chinese rural residents - Qianqian Zhang; Deyu Ren; Xuan Chang; Chen Sun; Ruyue Liu; Jialin Wang; Nan Zhang (Cancer Medicine, 2023)
Abstract Background This study examined the acceptance and willingness to pay (WTP) of rural residents toward packaging cancer screening (PCS) to provide a reference basis for promoting the screening sustainable development. Methods A face‐to‐face questionnaire survey was conducted among rural residents aged 40–69. The combination of double‐bounded dichotomous choices and open‐ended questions in the Contingent Valuation Method was used to guide participants' WTP. Logistic regression was used to explore the influencing factors of participants' screening acceptance, and Tobit model was used to analyze the associated factors of WTP. Results Of the 959 respondents, 89.36% were willing to accept PCS, but 10.64% stated unwillingness for the dominant reason that they did not attend clinics until symptom onset. Willingness to accept screening was significantly associated with region (Dongchangfu, OR = 0.251, 95%CI: 0.113~0.557; Linqu, OR = 0.150, 95%CI: 0.069~0.325), age with 60–69 (OR = 0.321, 95%CI: 0.126~0.816), annual income with 10,000–30,000 (OR = 1.632, 95%CI: 1.003~2.656) and having cancer‐screening experience (OR = 0.581, 95%CI: 0.371~0.909). And 57.66% of participants were willing to pay part of the screening cost among those willing to accept PCS. The residents' average WTP was ¥622, accounting for 20.73% of the total cost (¥3000). Willingness to pay for PCS was positively correlated with male gender, self‐employed occupation, residence in Feicheng (than Linqu), higher income, and having cancer‐screening experience. Conclusions Most rural residents were willing to accept free PCS, more than half of them were willing to pay part of the ¥3000 total cost, but their WTP‐values were low. It is necessary to carry out PCS publicity activities to improve public awareness and participation in precancerous screening. Additionally, for expanding the coverage and sustainability of screening, the appropriate proportion of rural residents to pay for screening costs should be controlled at about 20%, and governments, insurance and other sources are encouraged to actively participate to cover the remaining costs.